1995
DOI: 10.1089/cbr.1995.10.147
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Reactive Oxygen Species Production and Cytotoxicity in Human Neutrophilsin vitroand after Oral Administration of a Polyenzyme Preparation

Abstract: Polymorphonuclear neutrophils (PMN) can be primed for enhanced release of reactive oxygen species (ROS) by exposure to cytokines and biological response modifiers. ROS are considered to possess tumoricidal activity. The polyenzyme preparation Wobenzym (WE) contains pancreatin, papain, bromelain trypsin and chymotrypsin and is used in adjuvant tumor therapy. We investigated killing of WE-exposed PMN against tumor cells and analyzed WE influence on ROS production in a chemiluminescence assay in PMN in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 13 publications
2
15
0
1
Order By: Relevance
“…The positive results achieved by the administration of SET can be explained by favourable immunomodulatory effects of these preparations (Honzikova et al, 2004). Similar effects were also observed other authors (Helms and Miller, 2006;Lanchava et al, 2005;Zavadova et al, 1995). Interesting finding was also the observed improvement in spirometric lung function indices following the application of SET in children with recurrent obstructive bronchitis (Lanchava et al, 2005).…”
Section: Systemic Enzyme Therapysupporting
confidence: 85%
See 1 more Smart Citation
“…The positive results achieved by the administration of SET can be explained by favourable immunomodulatory effects of these preparations (Honzikova et al, 2004). Similar effects were also observed other authors (Helms and Miller, 2006;Lanchava et al, 2005;Zavadova et al, 1995). Interesting finding was also the observed improvement in spirometric lung function indices following the application of SET in children with recurrent obstructive bronchitis (Lanchava et al, 2005).…”
Section: Systemic Enzyme Therapysupporting
confidence: 85%
“…Enzymes bind to the blood antiproteases after resorption through the mucosa of gastrointestinal tract and then they are distributed to sites of inflammation where they modulate and restore the imbalance in immune responses. They are involved in the activation as non-specific as specific immunity mechanisms (Biziulevicius, 1998;Desser et al, 2001;Douwe, 2005;Manhart et al, 2002;Targoni et al, 1999;Zavadova et al, 1995;Zavadova & Desser, 1997). Enzyme therapy can change the expression of adhesion molecules and receptors on the surface of T lymphocytes, reduce the activation of many populations of immunocompetent cells and they increase the activation threshold of autoaggressive T-lymphocytes in the mechanism of specific immunity (Biziulevicius, 1998;Desser et al, 2001;Douwe, 2005;Lauer et al, 2001;Manhart et al, 2002;Targoni et al, 1999;Zavadova et al, 1995;Zavadova & Desser, 1997).…”
Section: Systemic Enzyme Therapymentioning
confidence: 99%
“…17 Finally, proteolytic enzymes influence the levels of antioxidant enzymes and reactive oxygen species. 18 Recently, a novel role for extracellular proteases as inhibitors of intracellular signal transduction pathways has been described. 5 …”
Section: Basis Of Evidence-based Complementary Medicine In Oncologymentioning
confidence: 99%
“…"These findings point to an immunomodulatory capacity of Wobenzym in adjuvant tumor therapy," she wrote. 50 1999. R. Kaul et al, of the SGPT Cancer Hospital, Indore, India, showed that Wobe-Mucos oral enzymes acted as potent anti-inflammatory and antiedematous agents, thereby decreasing acute toxic effects of radiation and increasing compliance and quality of life of cancer patients.…”
Section: Current Situationmentioning
confidence: 99%